2009
DOI: 10.1007/s11661-009-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

High-Cycle Fatigue Behavior of Microarc Oxidation Coatings Deposited on a 6061-T6 Al Alloy

Abstract: The objective of this article is to evaluate the influence of microarc oxidation (MAO) coatings on the high-cycle rotating bending fatigue behavior of the 6061-T6 aluminum alloy. Toward this purpose, the influence of the MAO coating process parameter (current density) and coating thickness on the fatigue life of the 6061-T6 Al alloy has been evaluated in the present study. In addition, the influence of the coating roughness on the fatigue life of the MAO-coated 6061-T6 Al-alloy sample has also been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…As a common point of observation to both the Al alloys, multiple predominant cracks can be noticed in the case of plain MAO coated fracture surface and fewer dominant cracks in the case of SP + MAO coatings . Furthermore, upon examination of a cross section for a fatigue test interrupted at 80% of experimentally measured life, the fatigue crack propagates almost like a straight line in the case of plain MAO coating (Figure ), while major crack deflection in the substrate region beneath the substrate‐coating interface as shown in Figure accompanied by multiple crack deflections of relatively smaller magnitude and crack‐branching as shown in Figure leads to major energy absorption and significantly increased fatigue life can be clearly noticed in the case of SP + MAO coatings . It may be noted that the SP induced compressive residual stresses beneath the substrate‐coating interface region of SP + MAO coating are the primary reason behind the deflection and branching of cracks as shown in Figures .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As a common point of observation to both the Al alloys, multiple predominant cracks can be noticed in the case of plain MAO coated fracture surface and fewer dominant cracks in the case of SP + MAO coatings . Furthermore, upon examination of a cross section for a fatigue test interrupted at 80% of experimentally measured life, the fatigue crack propagates almost like a straight line in the case of plain MAO coating (Figure ), while major crack deflection in the substrate region beneath the substrate‐coating interface as shown in Figure accompanied by multiple crack deflections of relatively smaller magnitude and crack‐branching as shown in Figure leads to major energy absorption and significantly increased fatigue life can be clearly noticed in the case of SP + MAO coatings . It may be noted that the SP induced compressive residual stresses beneath the substrate‐coating interface region of SP + MAO coating are the primary reason behind the deflection and branching of cracks as shown in Figures .…”
Section: Resultssupporting
confidence: 92%
“…However, the applications including landing gear components of aerospace sector often demand an additional property namely the fatigue resistance . The current state‐of‐art can only provide adequate wear and corrosion protection of Al alloys even when the advanced technologies such as micro arc oxidation (MAO) are deployed thereby leaving a clear space for developing the materials and processes that can simultaneously provide resistance against wear, corrosion and fatigue …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the DSC coating is also characterized by a lamellar structure characterized by weak inter-splat boundaries. Preliminary work by the present authors with MAO coated Al6061 alloy has indicated that even at 50% of the fatigue life, the crack has already reached the coatingsubstrate interface [21]. Based on the above observations, it can be postulated that the high cycle fatigue life of coated Al6061 alloy is largely determined/controlled by the propagation of the crack into the Al6061 alloy substrate from the coating-substrate interface.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, the influence of roughness of the MAO coating on its fatigue life has been specifically studied by the present authors [21] and it was observed that polishing the MAO coating surface to reduce its roughness from R a = 3.5 μm to R a = 0. All the above observations lead to the conclusion that the coating really does not provide any resistance to fatigue crack initiation.…”
Section: Discussionmentioning
confidence: 93%